Remote Sensing and Geospatial Approaches for Studying the Environment Affected by Human Activities - Li, Jun; Shen, Xinyi; Wu, Qiusheng; Zhang, Chengye (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over recent decades, intense human activities, including urban expansion, industrial emissions, farming, deforestation, mining, tourism, and land reclamation, have significantly transformed the natural environment. These changes give rise to environmental challenges like arable land degradation, deforestation, air and water pollution. Effective environmental protection and governance are crucial, particularly in environmentally vulnerable areas like farming-pastoral transitional zones, wetlands, arid regions, coastlines, and alpine-cold regions. Remote sensing proves invaluable in assessing environmental parameters and monitoring regional or global environmental changes over long-term history. Geospatial methods, grounded in remotely sensed images and other datasets, help analyze the compounded effects of multiple factors influenced by human activities. This reprint focuses on new theories, datasets, methods, findings, and applications to address essential questions about environmental changes. It explores how to monitor changes resulting from human activities, quantify their environmental impact, and assess the combined influence of natural disturbances and human alterations. The goal is to uncover patterns and mechanisms of environmental evolution, fostering knowledge exchange and innovative research for effective environmental protection and governance.